Efektivitas Distribusi Bantuan Pangan Nontunai (BPNT) kepada Keluarga Penerima Manfaat: Analisis Berdasarkan Indikator 6T dan Perspektif Ekonomi Islam - Sofiyah Nurus Sobah; Abdillah Mundir; Sukamto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Food intervention policies in Indonesia have evolved from a goods assistance scheme (Raskin/Rastra) to a cashless, digital-based aid (BPNT/Sembako). However, the effectiveness of this program in reducing the persistently high poverty rate of 9. 03% (BPS, 2024) in Kalirejo village remains questionable. This study aims to assess the effectiveness of BPNT distribution for Beneficiary Families (KPM) by utilizing the 6T indicators (Targeting, Quantity, Price, Timing, Administration, and Quality), alongside the perspective of distributive justice in Islamic Economics and Malthusian Theory concerning the disparities in local food availability. This research employs a descriptive qualitative approach through in-depth interviews and participatory observation of the implementation of the Prosperous Family Card (KKS) and the role of E-Warong. The findings indicate that the digitization of aid does enhance the flexibility and autonomy of KPM, but its effectiveness is hindered by digital infrastructure disparities, literacy barriers, and targeting errors (including both inclusion and exclusion errors). The study reveals that the current policy appears to prioritize distribution mechanisms (output) over economic empowerment (outcome). Theologically, the inaccuracies in data violate the principles of trust and distributive justice ('adl). The research concludes that digital transformation must be accompanied by strengthening local distribution chains and aligning social aid policies with sustainable economic empowerment programs to ensure the long-term welfare of the community